Enhancing Public Open Spaces: Exploring the Interplay of Perception, Safety and Security - Kaushal, Mayank (Calibrating Urban Livability in the Global South, 2024)
Public open spaces in urban environments play a pivotal role in enhancing community well-being and fostering a sense of connection among residents. These spaces, ranging from parks and plazas to community gardens and recreational areas, serve as essential components of the urban fabric. The significance of public open spaces lies in their multifaceted contributions to physical, mental, and social aspects of urban life. However, as urban populations continue to grow, the design and planning of urban spaces play a crucial role in shaping the overall well-being of residents. This study investigates the relationship between urban form, perceptions of safety and security, and their subsequent influence on the utilization of public open spaces. It aims to understand how these perceptions can be enhanced to foster a more inclusive, accessible, and appealing environment for a diverse range of users. The research employs a multi-dimensional approach, integrating qualitative and quantitative methodologies. Interviews, surveys, and observational analysis collect data on individuals' perceptions, experiences, and usage patterns within public open spaces. The study explores factors contributing to perceived safety and security, such as lighting, maintenance, surveillance, social dynamics, and design elements. Moreover, this research investigates strategies to improve perceptions of safety and security in public open spaces. It explores potential interventions, including urban design modifications, community engagement initiatives, technological advancements, and collaborative efforts among stakeholders. By identifying effective approaches to enhance these perceptions, this study provides valuable insights to create inviting, safe, and secure public open spaces that encourage active participation and improve overall urban livability.